A new species, Aster yaoshanensis (Asteracae, Astereae), from Guangxi (China), based on morphology and molecular phylogenetic data - Zheng, Xinyi; Qin, Kun; Li, Tingyu; Qu, Tianmeng; Luo, Junjia; Zhang, Guojin; Li, Bo; Li, Pan; Fu, Zhixi (Frontiers in Plant Science, 2024)
Aster yaoshanensis sp. nov. (Asteraceae) is described as a species new to science in this article. The new species grows in rock crevices of mountain valleys in Dayaoshan National Nature Reserve, Guangxi autonomous region, China. The molecular phylogenetic analysis, based on nuclear ribosomal DNA internal transcribed spacer (ITS) sequences and whole plastome, showed that the new species was placed in the Aster clade with high support. This new species is morphologically similar to A. jishouensis W.P. Li & S.X. Liu, but it can be easily distinguished from the latter by bract indumentum (glabrous except margin ciliate vs. villous especially on veins abaxially, glabrous adaxially) and color (green vs. purple), shorter corolla (3.2-3.5 mm vs. 4.5-5.3 mm), bract stalk (obvious, ca.1.2 mm vs. sessile), and different distribution (Guangxi vs. Hunan). A detailed description, distribution map, and wild photos are provided, and its morphology was compared with related species. The new species is currently known only from Guangxi, China.